THE EFFICIENCY OF THE UTILIZATION OF ELEMENTARY SELENIUM ADDITION TO THE RATIONS FOR CHICKENS - LARISA CAISÎN (Scientific Papers Animal Science and Biotechnologies, 2023)
Almost all off the fodders don't provide necessity in selenium. Micro supplements of selenium salts into chicken’s ration favor stimulation of growth. Necessity in producing of mixed food with supplement of selenium for chickens are obvious. In order to study the efficiency of the utilization of selenium addition in the chicken rations we have done a scientific and farm experiment. During the experiment an addition of selenium at the level 0.25mg/kg of dry substance with fodder and water was added to the rations of the chickens in the experimental group. The data on the live mass have shown that the live mass of the chickens in the experimental groups was greater in comparison with that in the control group. In our experiments, in using selenium supplements in mixed food for quick-growing chickens we also got positive results in body mass, spending of fodders and preservation, but it is necessary to continue research.